Peran Cerita Bergambar dalam Mengasah Kemampuan Bahasa Anak Usia Dini: Perspektif Kajian Cerita Anak - Fitri Andriani; Herlinda Herlinda; Nursalim Nursalim; Akmal Akmal; Vera Sardila (Universitas Maritim AMNI Semarang, 2024)
This article aims to examine the role of picture books in enhancing language skills in early childhood from the perspective of children's literature studies. Picture books are considered an effective medium in supporting children's language development because they combine visual and narrative elements that enrich the child's learning experience. Through picture books, children can not only develop vocabulary but also understand language structure, improve listening and speaking skills, and stimulate their imagination. This indicates that engaging and educational picture books can enhance children's language skills, particularly in word recognition, sentence development, and storytelling abilities. Therefore, picture books are a highly beneficial tool in improving language skills in early childhood and should be considered in early childhood education curricula.